Minimal state automata for detecting a ß globin gene mutation - Ferdania, Devi Fitri; Irawati; Garminia, Hanni; Akhmaloka; Rachmansyah, Kemal Aziez (Zielona Góra: Uniwersytet Zielonogórski)
Beta-thalassemia is an autosomal recessive blood disorder characterized by abnormalities in the synthesis of ß globin. Together with [alpha] globin, it is a subunit of globin protein, called hemoglobin, located inside our red blood cells to deliver oxygen from the lungs to all of the tissues throughout our body. Thereby, individuals with ß-thalassemia will often feel limp due to a lack of oxygen dissolved in their blood.
Keywords: minimal state automata; syntactic monoid; ß-thalassemia; biological sequences